PENGARUH IMPLEMENTASI MANAJEMEN BERBASIS MADRASAH TERHADAPKEDISIPLINAN GURU DI MIN KOTA BANDAR LAMPUNG - Erjati Abas (Ri'ayah: Jurnal Sosial dan Keagamaan, 2019)
The purpose of this study was to determine and analyze the effect of the implementation of Madrasah-Based Management on the discipline of teachers in MIN Kota Bandar Lampung. The method used is quantitative which aims to test hypotheses using statistical techniques. The data collection technique used is a questionnaire. The sample in this study amounted to 26 teachers in MIN City of Bandar Lampung. While the data analysis technique uses simple correlation statistical tests. The results of the research are that the better the implementation of Madrasah-Based Management will increase the discipline of Islamic Education teachers in MIN Bandar Lampung City. The strength of the influence of the implementation of Madrasah-Based Management on the discipline of Islamic Education teachers in MIN City of Bandar Lampung is 0.690 which is categorized as having moderate / moderate influence.